2007
DOI: 10.1159/000107464
|View full text |Cite
|
Sign up to set email alerts
|

House Dust and Storage Mite Extracts Influence Skin Keratinocyte and Fibroblast Function

Abstract: Background: The bodies of allergy-causing dust and storage mites likely contain many bioreactive molecules, including some that are allergenic. These molecules may penetrate the epidermis and dermis of the skin. However, little is known about the effects that most of the molecules from mites have on the function of cells in the skin, the overall inflammatory and immune reactions and the manifestation of allergic disease.The purpose of this research was to determine the response of cultured skin cells (keratino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 64 publications
4
43
0
Order By: Relevance
“…IL1R is an important mediator involved in many cytokine-induced immune and inflammatory responses. Moreover, overexpression of IL1R in both keratinocytes and fibroblasts has been shown to influence the pathophysiology of atopic dermatitis of skin (Arlian et al, 2008). H 2 O 2 treatment strongly enhanced the expression of IL1R, in accordance with previous studies (Higgins et al, 1999).…”
Section: Nannog Positively Regulated Genes Involves In Skin Texture Asupporting
confidence: 90%
“…IL1R is an important mediator involved in many cytokine-induced immune and inflammatory responses. Moreover, overexpression of IL1R in both keratinocytes and fibroblasts has been shown to influence the pathophysiology of atopic dermatitis of skin (Arlian et al, 2008). H 2 O 2 treatment strongly enhanced the expression of IL1R, in accordance with previous studies (Higgins et al, 1999).…”
Section: Nannog Positively Regulated Genes Involves In Skin Texture Asupporting
confidence: 90%
“…No differences were detected at baseline between the two groups; however, increased IL-8 and KC-like secretion levels were seen in atopic compared with healthy keratinocytes after stimulation. These data are in agreement with previous studies showing an increased production of proinflammatory cytokines by HDM (7,(22)(23)(24)(25). The different behaviours between the two keratinocyte populations suggest that atopic keratinocytes could respond excessively to environmental stimuli and that intrinsic alterations present in atopic keratinocytes, and not the presence of external proteases, may contribute to the excessive inflammatory response in AD.…”
Section: Discussionsupporting
confidence: 94%
“…Stimulated keratinocytes and fibroblasts produce and secrete multiple cytokines that promote cutaneous inflammation. Previous research has shown that house dust mite and stored product mite extracts stimulate the secretion of cytokines from cultured human dermal keratinocytes, fibroblasts and microvascular endothelial cells [20,21]. Both D. farinae and D. pteronyssinus extracts stimulate cultured keratinocytes to increase secretion of the chemokine growth-related oncogene-α (GROα, CXCL1), which is chemotactic for the extravasation of leukocytes during inflammation [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that house dust mite and stored product mite extracts stimulate the secretion of cytokines from cultured human dermal keratinocytes, fibroblasts and microvascular endothelial cells [20,21]. Both D. farinae and D. pteronyssinus extracts stimulate cultured keratinocytes to increase secretion of the chemokine growth-related oncogene-α (GROα, CXCL1), which is chemotactic for the extravasation of leukocytes during inflammation [20]. Likewise, D. farinae and/or D. pteronyssinus extracts induce cultured normal human dermal fibroblasts to secrete interleukin (IL)-6, IL-8 (CXCL8), monocyte chemoattractant protein-1 (MCP-1, CCL2) and macrophage colony-stimulating factor (M-CSF) [20].…”
Section: Introductionmentioning
confidence: 99%